Municipal entrepreneurship and energy policy : a five nation study of politics, innovation and social change /: a five nation study of politics, innovation and social change. (2019) - Woodward, Alison E, 1950-; Ellig, Jerome, 1962-; Burns, Tom R
No abstract available